2003
DOI: 10.1091/mbc.e03-04-0249
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Dynamics of Cdc2-Cyclin B during Meiotic Reinitiation in Starfish Oocytes

Abstract: The Cdc2-cyclin B kinase has a central role in regulating the onset of M phase. In starfish oocytes, Cdc2-cyclin B begins to be activated ϳ10 min after application of maturation hormone, followed by accumulation in the nucleus then nuclear envelope breakdown. By immunofluorescence and by expressing a green fluorescent (GFP) chimera of cyclin B, we find that cyclin B is present in aggregates in the cytoplasm of immature oocytes. The aggregates disperse at ϳ10 min, suggesting that the dispersal is closely relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…2H). This cortical distribution was reminiscent of that observed for cyclin B in Xenopus laevis (Beckhelling et al, 2003); and in keeping with the cytoplasmic accumulation observed in oocytes of other species (Terasaki et al, 2003;Westendorf et al, 1989) and in adult cells (Clute and Pines, 1999). Such cytoplasmic accumulation of cyclin B1 may be due to its ability to anchor to cytoplasmic proteins (Charrasse et al, 2000;Jackman et al, 1995;Ookata et al, 1995).…”
Section: Research Article Development 137 (8)supporting
confidence: 84%
“…2H). This cortical distribution was reminiscent of that observed for cyclin B in Xenopus laevis (Beckhelling et al, 2003); and in keeping with the cytoplasmic accumulation observed in oocytes of other species (Terasaki et al, 2003;Westendorf et al, 1989) and in adult cells (Clute and Pines, 1999). Such cytoplasmic accumulation of cyclin B1 may be due to its ability to anchor to cytoplasmic proteins (Charrasse et al, 2000;Jackman et al, 1995;Ookata et al, 1995).…”
Section: Research Article Development 137 (8)supporting
confidence: 84%
“…Studies in a number of cell types have indicated that the perinuclear/centrosomal region is the site of MPF accumulation (Bechelling et al, 2000). Recently, using cyclin B-GFP, it was shown that MPF enters the starfish nucleus starting from the animal pole side, which is the location of the centrosomes (Terasaki et al, 2003). The timing of its accumulation in the nucleus is consistent with its proposed role in disassembling the nuclear envelope, as the event takes place after the phosphorylation of the nuclear pore complexes (Macaulay et al, 1995).…”
mentioning
confidence: 66%
“…Another potential explanation for the induced aggregation is that the Cdks may be inherently prone to aggregation themselves. Cdk1-Cyclin B complexes exist in aggregates in Xenopus oocytes before resolubilizing and becoming active for the initiation of mitosis (30,31). Moreover, smaller and less frequent Cdk aggregates appear to be naturally present in some cell types, as they can be observed in vehicle-treated cells.…”
Section: Discussionmentioning
confidence: 99%